High‐silica deposits of an aqueous origin in western Hellas Basin, Mars - Joshua L. Bandfield (Geophysical Research Letters)
Data from the Thermal Emission Spectrometer and the Thermal Emission Imaging System have been used to identify isolated high silica surfaces in western Hellas Basin. Deconvolution results indicate that the surfaces are composed of nearly 80% high silica phases (amorphous silica, phyllosilicates, or zeolites). The deposits may be derived from alcoves in the terrain immediately to the north. The high silica deposits are an additional indicator of a variety of past aqueous processes on Mars.